PERENCANAAN BENDUNG DAERAH IRIGASI SISIRO KECAMATAN TENGGULUN KABUPATEN ACEH TAMIANG - Hutabarat, Hasurungan O.; Siregar, Syafiatun (Jurnal Insinyur Profesional, 2024)
The river basin of the irrigation weir originates from the Alur Bujuk with an area of 1.50 km2, to meet irrigation water needs as a proposed development of productive rice fields, the local community hopes to be able to utilize the flow of the Alur Bujuk and Alur Batu by building a bending. The bending construction was carried out to raise the water level in the channel so that it could be used for irrigation needs in the Sisiro Irrigation Area. This research aims to technically design a weir for water building requirements and hydraulic dimensions based on data availability and field analysis so that irrigation water needs for agriculture, especially rice crops, can be achieved. The results: 1) The number of weirs is 1 (one) unit with the Ogee weir type and is equipped with 2 (two) units of mud bags for the left irrigation network and the right irrigation network, 2) Width of the weir is 6.00 m, height of the dam is 2.50 m, slope of the weir beacon downstream section 1 : 1, planned flood discharge of 20 m3/sec, return period of 2 years, intake discharge of 0.27 m3/sec, 3) Number of tapping and final structures of 3 (three) units on the right network and 4 (four) units on the left network., 4) The number of quarter plots is 22 in the right network covering an area of 120.35 hectares and 21 units covering an area of 100.60 hectares in the left network, with a total irrigation area of 220.95 hectares., 5) The water distribution system in the Sisiro irrigation network must be carried out using rotation method because the mainstay flow in the Alur Bujuk is relatively small compared to the area of the irrigation area that must be irrigated so that planting time and patterns depend on the water withdrawal discharge.